A Missense Mutation of the Gene Encoding Synaptic Vesicle Glycoprotein 2A (SV2A) Confers Seizure Susceptibility by Disrupting Amygdalar Synaptic GABA Release - Tokudome, Kentaro; Okumura, Takahiro; Terada, Ryo; Shimizu, Saki; Kunisawa, Naofumi; Mashimo, Tomoji; Serikawa, Tadao; Sasa, Masashi; Ohno, Yukihiro (Frontiers in Pharmacology, 2016)
Synaptic vesicle glycoprotein 2A (SV2A) is specifically expressed in the membranes of synaptic vesicles and modulates action potential-dependent neurotransmitter release. To explore the role of SV2A in the pathogenesis of epileptic disorders, we recently generated a novel rat model (Sv2aL174Q rat) carrying a missense mutation of the Sv2a gene and showed that the Sv2aL174Q rats were hypersensitive to kindling development (Tokudome et al., 2016). Here, we further conducted behavioral and neurochemical studies to clarify the pathophysiological mechanisms underlying the seizure vulnerability in Sv2aL174Q rats. Sv2aL174Q rats were highly susceptible to pentylenetetrazole (PTZ)-induced seizures, yielding a significantly higher seizure scores and seizure incidence than the control animals. Brain mapping analysis of Fos expression, a biological marker of neural excitation, revealed that the seizure threshold level of PTZ region-specifically elevated Fos expression in the amygdala in Sv2aL174Q rats. In vivo microdialysis study showed that the Sv2aL174Q mutation preferentially reduced high K+ (depolarization)-evoked GABA release, but not glutamate release, in the amygdala. In addition, specific control of GABA release by SV2A was supported by its predominant expression in GABAergic neurons, which were co-stained with antibodies against SV2A and glutamate decarboxylase 1. The present results suggest that dysfunction of SV2A by the missense mutation elevates seizure susceptibility in rats by preferentially disrupting synaptic GABA release in the amygdala, illustrating the crucial role of amygdalar SV2A-GABAergic system in epileptogenesis.